Peran Rumah Pintar Pemilu Dalam Meningkatkan Partisipasi Masyarakat Pada Pemilu Serentak - Anugrah P. Telaumbanua; Marlon Marlon; Heri Kusmanto (Universitas Medan Area, 2021)
The purpose of this article is to analyze the role of the KPU Binjai City in carrying out the RPP in conducting voter education to the public and analyzing the success of the RPP in increasing public voter participation in Binja City in the 2019 Election. This research uses descriptive analysis research, which aims to provide a description of Research subjects based on data from the variables obtained from the group of subjects studied were about RPP in increasing voter participation, which requires a number of data and descriptions qualitatively to support the research results. The results showed that the Binjai KPU in the 2019 election has played a role as a facilitator, socializer to expand information and the election agenda. The RPP of Binjai City in increasing voter participation in the 2019 election. The participation rate increased by 7.92% from 74.34% to 82.26% for Pileg while for the implementation of the 2019 presidential election the participation rate increased by 16.91% from 65.68 % to 82.59%.